2022
DOI: 10.7759/cureus.23242
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of Cervical Dysplasia in a University Hospital Using Pap Smear and Colposcopy in the Western Region of Saudi Arabia: A Correlational Study

Abstract: Objectives To assess the diagnostic performance of Pap smear screening with or without human papillomavirus (HPV) testing and colposcopy in detecting preinvasive lesions of the cervix among women with reference to histopathological findings. Materials and methods We performed a retrospective study in a tertiary care center of the clinical and pathological records of women with evocative symptomatology. The diagnostic performance of Pap smear screening and colposcopy was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…After excluding asymptomatic and healthy cervix cases, the most commonly reported clinical symptoms and examination findings are white discharge per vaginum, abdominal pain, abnormal bleeding, postcoital bleeding, irregular cycle, postmenopausal bleeding, intermenstrual bleeding, hypertrophied cervix, cervical erosion, bleed on touch cervix, and uterovaginal prolapse. [ 5 , 6 , 8 , 9 ] We observed white discharge per vaginum, abdominal pain, cervical mucoid discharge, and irregular cycle as common clinical symptoms, and cervical erosion, cervical hypertrophy, and bleed on touch cervix as common examination findings. In 2014 Bethesda System, the “Epithelial cell abnormality: Squamous” includes squamous intraepithelial lesion (SIL) category, which comprises a spectrum of squamous cell lesions starting from the precancerous lesions of LSIL to HSIL and invasive squamous cell carcinoma (SCC).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…After excluding asymptomatic and healthy cervix cases, the most commonly reported clinical symptoms and examination findings are white discharge per vaginum, abdominal pain, abnormal bleeding, postcoital bleeding, irregular cycle, postmenopausal bleeding, intermenstrual bleeding, hypertrophied cervix, cervical erosion, bleed on touch cervix, and uterovaginal prolapse. [ 5 , 6 , 8 , 9 ] We observed white discharge per vaginum, abdominal pain, cervical mucoid discharge, and irregular cycle as common clinical symptoms, and cervical erosion, cervical hypertrophy, and bleed on touch cervix as common examination findings. In 2014 Bethesda System, the “Epithelial cell abnormality: Squamous” includes squamous intraepithelial lesion (SIL) category, which comprises a spectrum of squamous cell lesions starting from the precancerous lesions of LSIL to HSIL and invasive squamous cell carcinoma (SCC).…”
Section: Discussionmentioning
confidence: 89%
“…observed that mean age of the study population was 31.55 ± 6.66 years (ranging from 21 to 60 years) and 45.12 ± 6.66 years (ranging from 21 to 75 years), respectively. [ 6 , 8 ] The age range in our study was 21–80 years, with a mean age of 38.89 years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, HPV DNA tests offer a molecular snapshot of HPV infection, providing insights into an individual's susceptibility to cervical cancer development. Equipped with this understanding, medical experts can proactively intervene, either through surveillance or treatment, halting the progression of precancerous lesions [69] [70].…”
Section: Rtbs-2023mentioning
confidence: 99%